Sosialisasi Peranan Lembaga Adat dalam Menyelesaikan Pelanggaran Adat di Kaseupahan Sinar Resmi Kabupaten Sukabumi - Puti Priyana; Tanumihardja Jopie Gunawan; Wienike Dinar Pratiwi (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
Kaseuphan Sinar Official adopts the common law style, showing the usual characteristics of the common law community itself. Issues of violations and incidents affect not only modern nations, but also indigenous peoples as well as areas of social service. There is a moral system that acts as a countermeasure and as a place to settle violations. Communities that are Target Partners of Community Service should facilitate the role of traditional institutions and resolution of common cases in ​​Target Partners of Community Service so that future Target Partners of Community Service can take advantage of traditional institutions. It is expected that you will understand and be able to understand. It is suitable for the courts of the Indonesian state. And beyond that, in disputes involving children or within the framework of common law. It is hoped that eligible community service partners will be able to learn more about how to handle common cases involving children. Additionally, even after socialization and modules, the community expected that target partners of her services have knowledge of child protection law (such as rights and responsibilities) as an integral part of the target partner environment of the service. will be as a result, we found that the targeted community service partners were very enthusiastic about carrying out this activity, which was reflected in the various questions posed to the resource personnel. This community service provides an overview of the community services team working to maximize the role of traditional institutions in Karawang Regency's Sinar Official Village and reduce the number of child protection violations in the area.